Attitude of community members towards the capacity of the village land councils in managing land use conflicts between farmers and pastoralists in Tanzania: A cross sectional case study analysis - Homera , Juma Zuberi; Mollel, Henry A. (E-palli publishers, 2024)
A research article submitted to the American Journal of Agricultural Science, Engineering, and Technology (AJASET) Volume 8 Issue 2, Year 2024